2016
DOI: 10.3233/jad-151072
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Perceptions of Research in Aging and Dementia in an Urban Minority Population

Abstract: In dementia trials, minority participation is low. We assessed attitudes toward research in a community based urban poor minority sample of elderly adults attending senior center talks using the 7-item Research Attitudes Questionnaire (RAQ). Presentations on cognitive aging were given at senior centers, and 123 attendees completed the RAQ-7. On trust and safety questions, a significant minority (42-48%) responded neutrally or negatively. Encouragingly, on questions concerning the importance of research, 72-81%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…One study specified targeting a racially diverse population, achieving a 29% non-white sample [34]. Four of 22 studies reported participant income [36,42,44,46], and two studies focused specifically on engaging people from “poor” backgrounds [51] or within “disadvantaged or underserved” areas [20]. No studies focused on or included Native American/Alaskan Native or Pacific Islander populations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study specified targeting a racially diverse population, achieving a 29% non-white sample [34]. Four of 22 studies reported participant income [36,42,44,46], and two studies focused specifically on engaging people from “poor” backgrounds [51] or within “disadvantaged or underserved” areas [20]. No studies focused on or included Native American/Alaskan Native or Pacific Islander populations.…”
Section: Resultsmentioning
confidence: 99%
“…Four of 22 studies reported participant income [36,42,44,46], and two studies focused specifically on engaging people from “poor” backgrounds [51] or within “disadvantaged or underserved” areas [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neugroschl et al. [33] administered the RAQ to 123 diverse attendees of community talks on cognitive aging in New York City and found that nearly half of participants had a less than positive response for the item “participating in medical research is generally safe.” The authors noted that these scores were lower than previously reported means from predominantly white participants [34] .…”
Section: Discussionmentioning
confidence: 99%